PERAN MEDIA SOSIAL DALAM MENINGKATKAN KESADARAN GAYA HIDUP SEHAT PADA REMAJA - Sakinah Rahmawaty; Eti Hanifah Tamba; Usiono (Jurnal Penelitian Pendidikan Indonesia (JPPI), 2025)
Adolescents face a variety of health problems, including obesity, which is on the rise due to unhealthy diets and sedentary lifestyles. This study aims to explore the role of social media in increasing healthy lifestyle awareness among adolescents. Using a descriptive qualitative method, interviews were conducted with several teenage respondents to collect data regarding their perceptions of health content on social media. The results showed that many respondents felt motivated to change their habits, such as increasing vegetable and fruit consumption and exercising regularly after being exposed to educational content. However, challenges in maintaining consistency remain. Therefore, there is a need to increase the amount of educational and useful health content, as well as the importance of obtaining information from trusted sources to avoid the influence of unhealthy trends. Adolescent health promotion should consider the influence of social media and emphasize the importance of mental and emotional health in an effort to improve adolescent well-being.